Resistance to Information Literacy: Potential Causes Among Undergraduate University Students - Lamoureux, Isabelle (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The author investigates the potential cognitive factors responsible for university students’ resistance to information literacy (IL). Previous research explored different possible cognitive factors but so far no causal relationship has been established. The author, by asking students’ personal opinions, is hoping to discover a relationship in order to improve the design of IL learning interventions. L’auteure se penche sur les possibles facteurs cognitifs responsables de la résistance des étudiants universitaires à la maîtrise de l’information. Des études ont déjà exploré différents facteurs cognitifs possibles, mais aucune relation causale n’a encore été établie. En demandant l’opinion personnelle des étudiants, l’auteure espère découvrir un lien afin d’améliorer le design des séances d’intervention en maîtrise de l’information.